Health equity in the New Zealand health care system: a national survey - Doughty Robert; Devlin Gerard; Clinton Janet; Carswell Peter; Boyd Mary Anne; Barber P Alan; Mahony Faith; Connolly Martin J; Kenealy Timothy W; Sheridan Nicolette F; Dyall Lorna; Kerse Ngaire; et al. (BMC, 2011)
Abstract Introduction In all countries people experience different social circumstances that result in avoidable differences in health. In New Zealand, Māori, Pacific peoples, and those with lower socioeconomic status experience higher levels of chronic illness, which is the leading cause of mortality, morbidity and inequitable health outcomes. Whilst the health system can enable a fairer distribution of good health, limited national data is available to measure health equity. Therefore, we sought to find out whether health services in New Zealand were equitable by measuring the level of development of components of chronic care management systems across district health boards. Variation in provision by geography, condition or ethnicity can be interpreted as inequitable. Methods A national survey of district health boards (DHBs) was undertaken on macro approaches to chronic condition management with detail on cardiovascular disease, chronic obstructive pulmonary disease, congestive heart failure, stroke and diabetes. Additional data from expert informant interviews on program reach and the cultural needs of Māori and Pacific peoples was sought. Survey data were analyzed on dimensions of health equity relevant to strategic planning and program delivery. Results are presented as descriptive statistics and free text. Interviews were transcribed and NVivo 8 software supported a general inductive approach to identify common themes. Results Survey responses were received from the majority of DHBs (15/21), some PHOs (21/84) and 31 expert informants. Measuring, monitoring and targeting equity is not systematically undertaken. The Health Equity Assessment Tool is used in strategic planning but not in decisions about implementing or monitoring disease programs. Variable implementation of evidence-based practices in disease management and multiple funding streams made program implementation difficult. Equity for Māori is embedded in policy, this is not so for other ethnic groups or by geography. Populations that conventional practitioners find hard to reach, despite recognized needs, are often underserved. Nurses and community health workers carried a disproportionate burden of care. Cultural and diversity training is not a condition of employment. Conclusions There is a struggle to put equity principles into practice, indicating will without enactment. Equity is not addressed systematically below strategic levels and equity does not shape funding decisions, program development, implementation and monitoring. Equity is not incentivized although examples of exceptional practice, driven by individuals, are evident across New Zealand.